Microbiome variability and role of Candida albicans in site-specific dental plaques in orthodontic adolescent patients with white spot lesions - Hao Yang; Hongyu Gao; Xianju Xie; Hongmei Wang; Xiaowei Li; Qingchen Qiao; Yansong Ma; Yuxing Bai (Journal of Oral Microbiology, 2025)
White spot lesions (WSLs) are a common complication of orthodontic treatment. However, the cariogenic discrepancy in the supragingival microbiome between demineralized and non-demineralized surfaces and the influence of Candida albicans associated with WSLs remain unexplored. This study investigated the changes in supragingival microbiome of orthodontic adolescents with WSLs, encompassing both demineralized and non-demineralized sites, and explored C. albicans colonization in these patients. Supragingival plaques were collected from 29 orthodontic adolescents with WSLs (categorized into demineralized and non-demineralized groups based on the presence/absence of demineralization at sampling sites) and 23 healthy orthodontic adolescents. Supragingival microbiome composition was evaluated using 16S rRNA sequencing, and C. albicans colonization was identified using fungal culture methods. The supragingival microbiome on non-demineralized surfaces showed intermediate cariogenic potential between demineralized and healthy states, but closer to the demineralized state. C. albicans exhibited a propensity for colonization in WSLs patients without site-specificity. C. albicans influenced bacterial composition, with Streptococcus mutans significantly enriched on the demineralized surfaces of C. albicans-positive patients. In orthodontic adolescents with WSLs, non-demineralized surfaces showed microbiome shifts, necessitating interventions to promote a healthy microbiome. C. albicans can impact microbiome composition and potentially contribute to WSLs pathogenesis.